(untitled) (International Journal of Engineering and Computer Science, 2017)
Increasing lifetime in wireless sensor networks is a major challenge because the nodes are equipped with low power battery. For increasing the lifetime of the sensor nodes energy efficient routing is one solution which minimizes maintenance cost and maximizes the overall performance of the nodes LEACH (Low-Energy Adaptive Clustering Hierarchy), a clustering-based protocol that utilizes randomized rotation of local cluster base stations (cluster-heads) to evenly distribute the energy load among the sensors in the network. Incorporates data fusion into the routing protocol to reduce the amount of information that must be transmitted to the base station. In addition, LEACH is able to distribute energy dissipation evenly throughout the sensors, doubling the useful system lifetime for the networks we simulated. Also we call the proposed protocol as RESIDUAL ENERGY EFFICIENT PROTOCOL as modification in the basic LEACH protocol in terms of residual energy (ratio of energy in current round to total energy of the network) of nodes. Since LEACH has many drawbacks, many researchers have tried to make this protocol performs better by improving cluster head selection algorithm by several parameters. LEACH stochastic cluster head selection algorithm is extended by adjusting the threshold T (n). Considering these parameters, simulation results shows that the proposed protocol REAP 1 and REAP 2 could better reduce energy consumption and prolong lifetime of the wireless sensor network with respect to the parameters FND (First Node Dies), HND (Half Node Dies) and LND (Last Node Dies) comparative to LEACH , NEAP-1 and NEAP -2.